The Development of Arabic Language Learning Media Using Wordwall for Madrasah Ibtidaiyah - Mahardini, Angger Putri; Qiftiyah, Maratul; Asriyah, Masfiyatul; Firdausi, Hanifah (al-Ittijah: Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2025)
This study aims to develop Arabic language learning media using Wordwall to support instructional effectiveness at the Madrasah Ibtidaiyah level. The research employed a Research and Development (R&D) approach using the ADDIE model, comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. Expert validations by content and media specialists indicated that the developed media is very valid. Practicality tests conducted with students and teachers revealed that the media is highly practical for classroom implementation. The interactive features of Wordwall were found to enhance student engagement and facilitate vocabulary acquisition. The findings suggest that the media is not only valid and practical but also contributes to improving the quality of Arabic language instruction in Madrasah Ibtidaiyah through the integration of technology-based learning tools.